ADENOID HYPERTROPHY IN ADULT PATIENTS AND ITS RELATION WITH ALLERGY - Nasrat Al-juboori, Ahmad; Fadhil, Assad; Sahib, Nawar (European Scientific Journal, ESJ, 2014)
Aims: To evaluate the clinical significance of adenoid hypertrophy(AH) in adult patients and its relation with allergy.Study Design: Case series study.Place and Duration of Study: This study was done in Al-Ramadi and Al-Fallujah Teaching Hospitals in Al-Anbar Governorate, Iraq, during theperiod from February 2003 to August 2012.Methodology: Adult patients(6538 patients) suffered from nasal obstruction, 12 of them found to haveAH. The diagnosis was made in different ways, some were diagnosedpreliminary by history and clinical examination, nasolaryngoscopy, andradiography, in others the diagnosis done by accidental finding duringoperations for septal and sinuses pathology. In above groups of patientsadenoidectomy were performed, and in remaining patient, excisional biopsywas done for a postnasal space mass diagnosed provisionally asangiofibroma. Follow up continued for one year after surgery. Results: Out of 12 patients aged between I8-36 years with AH, four patientswere diagnosed preoperatively, another seven patients the diagnosisdiscovered peroperatively during operations for septal and sinuses pathology.The AH represented in 0.18% of the causes of nasal obstruction in adults.Allergic manifestations and positive skin test occurred in 66% of the studiedpatients.Conclusion: From this study we concluded that, AH in adult patients wasrare and there was significant relationship with allergy.